Training and Self-Efficacy on Organizational Commitment with Job Satisfaction Mediation at PUPR Bali - A A Sg Eli Pertami Dewi Saraswati; Ni Made Dwi Puspitawati; Ni Putu Cempaka Dharmadewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In the midst of increasing organizational competition, issues of low organizational commitment remain prevalent, including at the Office of Public Works, Spatial Planning, Housing, and Settlement Areas of Bali Province, as indicated by a high absenteeism rate and ineffective work behaviors. These problems are suspected to be influenced by inadequate training methods, low self-efficacy among employees, and a lack of job satisfaction. The present study explores the extent to which employee training and perceived self-efficacy contribute to fostering organizational commitment, with job satisfaction positioned as an intervening construct. Conducted within the context of the Public Works, Spatial Planning, Housing, and Settlement Agency of Bali Province, the research engaged a workforce population of 610 individuals. Through the application of the Slovin formula, a representative sample of 86 respondents was identified. Data were gathered through a combination of structured questionnaires, in-depth interviews, and document review. Analytical processing was undertaken using path analysis to model the causal relationships among variables. The empirical evidence revealed that both training initiatives and self-efficacy perceptions have a favorable and statistically significant relationship with employees’ commitment to the organization. These two factors were also found to positively affect job satisfaction. Furthermore, job satisfaction emerged as a critical determinant that reinforces organizational commitment. The analysis further supports the mediating role of job satisfaction, demonstrating that the influence of training and self-efficacy on organizational commitment is also conveyed indirectly through improved job satisfaction levels. The findings of this study highlight the importance of investing in employee development through effective training programs and boosting self-efficacy to enhance job satisfaction.